Wybrane problemy teorii mnożnika handlu międzynarodowego - Barczyk, Ryszard (Wydział Prawa i Administracji UAM, 1982)
The concept of multiplier of the international tirade serves as a theoretical and model plane to formulate the quantitative relations between, changes in exports and imports and changes in the internal effective demand, being the main factor changing a course of business cycle in the modern capitalist economic system. This paper attempts at systematization of theoretical propositions formulated by non-Marxist economists which form the static and dynamic theory of multiplier of the international trade. The article contains two parts: the first one presents the static theory of the multiplier describing and comparing values of the dependent variable in the two situations of equilibrium of the systems differing from each other in values of their independent variable. The second part accounts for the dynamic conditions which can present the influence of the increase or decline of exports and imports on the dynamics of the national income of the analysed capitalist economy in each period of time as well as the final limits of changes of the dependent values. The systematizing analysis of propositions constituting the theory of multiplier of the international trade proved that the discussed mechanism can explain the interrelations between the changes of international trade and the changes of the internal effective demand of the examined capitalist economy only to a lesser degree. The power of explanation of that conception is highly limited as it does not expound the mechanism of appearance of incentives in the business cycle in export and in import, it cannot be applied when there is a full utilization of factors of production and it does not take account of the qualitative apects and the influence of the external trend of business on a given economy through the foreign trade.
The Theory of Multiplier of the International Trade in the Modern Capitalist Economic System